The real effect of legal institutions: Environmental courts and firm environmental protection expenditure - Zhang, Qi; Yu, Zhi; Kong, Dongmin (Journal of environmental economics and management, 2019)
This paper evaluates the real effects of environmental justice reform on environmental governance at the firm level. Using the establishment of environmental courts in China as a quasi-natural experiment, our difference-in-differences estimation shows that: (1) environmental courts significantly enhance environmental investment by firms, and this relationship is robust to different specifications and alternative measures; (2) three possible channels are the improved levels of justice and enforcement of environmental protection, and the mitigation of local government intervention; (3) our findings are particularly pronounced in subsamples with severe local protectionism, state-owned enterprises (SOEs), and non-SOEs with political connections; (4) at the city-level, environmental courts significantly increase air quality and promote cities to cross the inflection point of the environmental Kuznets curve earlier. Overall, this paper reveals the micro-mechanisms behind the real effects of environmental justice on firm environmental investment, thus providing timely implications for regulators concerned with environmental protection.